Integral values of biomass and stock of zooplankton in the epipelagic layer of the area 71 in the North Pacific, including the Bering and Okhotsk Seas, and patterns of distribution for mass species - Anatoly F. Volkov (Известия ТИНРО, 2015)
The Okhotsk and Bering Seas and the subarctic zone of the North Pacific are surveyed well by the expeditions conducted by Pacific Fish. Res. Center (TINRO) in the last three decades (115 surveys in 1984-2013), with sampling of zooplankton for monitoring of feeding resources of commercial species. Mean total zooplankton biomass and biomasses of size fractions of zooplankton, its taxonomic groups and mass species are calculated, by biostatistical areas. General patterns of the biomass distribution between the biostatistical areas are determined and presented as the charts of the biomass averaged by the areas. The most abundant species of zooplankton with similar systematic and trophic status are spatially separated that allows them to reduce competition for food, for example the pairs of small-sized, medium-sized and large-sized Copepoda species ( Pseudocalanus minutus - Oithona similis, Metridia pacifica - M. okhotensis , Calanus glacialis - Neocalanus plumchrus ), the pair of Hyperiida species ( Themisto pacifica - T. libellula ) and four Euphausia species ( Thysanoessa raschii - Th. inermis - Th. longipes - Euphausia pacifica ) in the Okhotsk Sea. Detailed tables on biomass and stock of the main components of zooplankton are presented, by regions and biostatistical areas.